Brit in the FBI : The Sixth Day - Book 5 Book 5 - Coulter, Catherine; Ellison, J. T. (New York : Gallery Books, 2018)
"When several major political figures die mysteriously, officials declare the deaths are from natural causes. Then the German Vice-Chancellor dies on the steps of 10 Downing Street, and a drone is spotted hovering over the scene. The truth becomes clear--these high-profile deaths are well-constructed assassinations, and the Covert Eyes team is tasked to investigate. With the help of Dr. Isabella Marin, a young expert in the enigmatic Voynich Manuscript and cryptophasia, ... Nicholas and Michaela home in on Roman Ardelean, a wealthy cybersecurity genius and a descendant of fifteenth century Romanian Vlad the Impaler- -often romanticized as Dracula"--
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Intelligence officers -- Fiction; Assassination -- Investigation; Fiction; Drone aircraft -- Fiction; Revenge -- Fiction; London (England) -- Fiction; Mystery